Role of Competition in Growing Markets: Telecom Sector - Srivastava, R.; Bhangle, Jatin; Bhatt, Nirav; Gogri, Kunal; Marfatia, Hemal (Indian Journal of Marketing, 2006)
This paper studies the booming service sector. The focus is on the cellular service providers in the country. As the topic suggests 'the role of competition in growing markets' an industry, which is in the growth stage, has been identified. The theory of product life cycle is explained with emphasis on the growth stage. It then studies the marketing strategies adopted by the major players like Bharti, Reliance, Orange, Tatas etc.. It also tries to show how in the product life cycle the various service providers are trying to fit in their products and services. The analysis of the survey puts into perspective the role of competition in the in the telecom industry.